Four new species of Entoloma subgenus Cyanula (Entolomataceae, Agaricales) from subtropical regions of China - Lin-Gen Chen; Hong Chen; Ling Ding; Yu-Qin Xu; Hui Zeng; Sheng-Nan Wang; Jun-Qing Yan (MycoKeys)
In this study, four species of Entoloma subgenus Cyanula (E. orientosinense, E. subgriseosquamulosum, E. subpraegracile, and E. wuyishanense) from subtropical regions of China, are described as new to science based on morphological and phylogenetic analyses. Morphologically, E. orientosinense is characterized by the white basidiomata, relatively large basidiospores, and carneogriseum-type lamellae edge; E. subgriseosquamulosum is recognized by the fuscous pileus, crowded and adnate lamellae, and medium-sized basidiospores; E. subpraegracile is identified by the yellow pileus and intervenose lamellae with sterile or heterogeneous edge; E. wuyishanense is distinct by the blue basidiomata and fertile lamellae edge with slightly bluish pigmentation near the stipe. Entoloma orientosinense belongs to sect. Caesiocincta, subsect. Queletia, and E. wuyishanense belongs to sect. Poliopodes. The remaining two species each form independent branches and do not belong to any known sections. Detailed descriptions, color photos, and a key to related species are presented.